Short‐Term Effects of Albendazole on the Oxidative Stress Markers and Hematological Parameters in Tissues of African Catfish Clarias gariepinus. Issue 4 (18th October 2016) - Nwani, Christopher Didigwu; Odo, Gregory Ejike; Nwadinigwe, Alfreda O.; Onyeke, Christopher C.; Atama, Chinedu Ifeanyi; Ngwu, Godwin; Oluah, Stanley N.; Ukonze, Juliana Adimonye; Ezeibe, Bridget Chidi A.
Abstract: Albendazole (ABZ) is a typical broad‐spectrum benzimidazole drug used for the treatment of parasitic worm infestations in humans and animals. The present study investigated the oxidative stress biomarkers and hematological parameters in juvenile African Catfish (also known as Sharptooth Catfish) Clarias gariepinus exposed to ABZ for 96 h. Fish were exposed to 0 (control) 20, 40, and 60 mg/L ABZ. The liver and gill tissues were sampled at regular intervals of 24 h, and the results showed significant concentration‐ and time‐dependent increases in the values of lipid peroxidation but reductions in glutathione peroxidase, catalase, superoxide dismutase, and glutathione reductase in both tissues. Erythrocytes were sampled to evaluate hematological parameters. The results showed significant concentration‐ and time‐dependent increases in white blood cells but no significant differences in mean cellular hemoglobin. Hemoglobin values, red blood cell counts, packed cell volume, mean cell volume, and mean cellular hemoglobin concentration decreased significantly over the experimental period. The activities of lymphocytes and neutrophils increased significantly, whereas there were no significant differences in basophils, eosinophils, and monocytes among the treatment groups. Albendazole should be used with caution, as sublethal concentrations induced oxidative stress in the liver and gill tissues along with hematological changes that were more evident in liver cells. Received November 20, 2015; accepted May 4, 2015 Published online October 18, 2016